Meconium-Stained Amniotic Fluid and Its Perinatal Feto-maternal Outcome - Rahman, Md Mahbubur; Amin, Abdullah Al; Quader, Md Abdul (Community Based Medical Journal, 2022)
Meconium Stained Amniotic Fluid is associated with increased risk of operative delivery or caesarean section and increased rate of neonatal resuscitation, morbidity and mortality. A hospital-based prospective, observational study was conducted in the Obstetrics & Gynecology Department, NICU and Neonatal Ward of Naval Base Hospital, a tertiary care hospital of Bangladesh Navy, Chattogram, Bangladesh, between January 2020 and December 2021. A semi-structured questionnaire was prepared for both case and control group. 182 cases were enrolled as case and another 182 cases were as control. Antenatal checkup was significantly less in cases (p<0.05). Mean weight was 2.8±0.4 Kg in cases and in control 2.7±0.5 Kg (p<0.01). Mean fetal heart rate were 140±10.5 beats/min in cases and in control 135.7±7.2 beats/min (p<0.01). Apgar scores at 1st minute and fifth minutes were significantly lower in cases (7±1.4 and 8.2±1.2 respectively) in comparison to control (7.5±0.3 and 9.2±1.1 respectively). Obstetric outcome of labor, that is mode of delivery was significantly dictated by the presence of MSAF. There were more than half (57.1%) of the cases were having grade three MSAF, whereas grade one and grade two were 14.8% and 28% respectively. Perinatal asphyxia, 5 min APGAR score <7, oropharyngeal suction needed, EONS, MAS, admission in NICU/Neonatal ward and neonatal death all were significantly higher in MASF group. MSAF is associated with increased need for neonatal resuscitation, higher risk of perinatal asphyxia, MAS, hospital admission and mortality for fetus and higher risk for operative delivery. CBMJ 2022 July: vol. 11 no. 02 P: 114-119